1985
DOI: 10.1111/j.1432-1033.1985.tb08674.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced 6,6,8‐Trimethylpterins

Abstract: The substrates of dihydropteridine reductase (EC 1.6.99.7), quinonoid 7,8‐dihydro(6H)pterins, are unstable and decompose in various ways. In attempting to prepare a more stable substrate, 6,6,8‐trimethyl‐5,6,7,8‐tetrahydro(3H)pterin was synthesised and the quinonoid 6,6,8‐trimethyl‐7,8‐dihydro(6H)pterin derived from it is extremely stable with a half‐life in 0.1 M Tris/HCl (pH 7.6, 25°C) of 33 h. Quinonoid 6,6,8‐trimethyl‐7,8‐dihydro(6H)pterin is not a substrate for dihydropteridine reductase but it is reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…5,8-Dihydrpterins have been observed only transiently during electrochemical reductions and have not been characterized (Kwee & Lund, 1973). As for 8-substituted quinonoid-dihydropterins (Randles & Armarego, 1985;Armarego et al, 1986), 8-methyl-5,8-dihydropterin would be expected to rearrange rapidly (Kwee & Lund, 1973) to the 7.8-dihydro tautomer: our previous theoretical calculations suggested that 5,8-dihydropterin would be ~11 kcal mol™1 less stable than 7,8-dihydropterin (Gready, 1985b). On mecha-Thibault et al…”
Section: Discussionmentioning
confidence: 99%
“…5,8-Dihydrpterins have been observed only transiently during electrochemical reductions and have not been characterized (Kwee & Lund, 1973). As for 8-substituted quinonoid-dihydropterins (Randles & Armarego, 1985;Armarego et al, 1986), 8-methyl-5,8-dihydropterin would be expected to rearrange rapidly (Kwee & Lund, 1973) to the 7.8-dihydro tautomer: our previous theoretical calculations suggested that 5,8-dihydropterin would be ~11 kcal mol™1 less stable than 7,8-dihydropterin (Gready, 1985b). On mecha-Thibault et al…”
Section: Discussionmentioning
confidence: 99%
“…Tetrahydropterins are generally unstable in air towards oxidation to a dihydro state followed by rapid rearrangement to the stable 7,8-dihydro tautomer. It has been observed that the rearrangement is blocked by disubstitution at the 6 position permitting isolation of a quinonoid tautomer of dihydropterin [64,65]. …”
Section: Pterin Redox Chemistrymentioning
confidence: 99%
“…In general terms, the pyrimidine portion of the pterin ring is most essential. However, several deviations in this part of the pterin nucleus do not abrogate PAH activity, including monomethylation of the exocyclic N 2 group, replacement of the C 4 carbonyl by an amino group, and monomethylation of N 8 (6,6,8-trimethyl-PH 4 is nonfunctional with TyrH, however) …”
Section: Cofactor Requirements1 Biopterin Analogues and Pyrimidinesmentioning
confidence: 99%